A novel continuous model to approximate time Petri nets: Modelling and analysis - Gu, Tianlong; Dong, Rongsheng (Zielona Góra: Uniwersytet Zielonogórski)
In order to approximate discrete-event systems in which there exist considerable states and events, David and Alla define a continuous Petri net (CPN). So far, CPNs have been a useful tool not only for approximating discrete-event systems but also for modelling continuous processes.
Keywords: continuous Petri nets; hybrid systems; discrete event systems